2018
DOI: 10.1039/c7lc01217a
|View full text |Cite
|
Sign up to set email alerts
|

Injection molded lab-on-a-disc platform for screening of genetically modified E. coli using liquid–liquid extraction and surface enhanced Raman scattering

Abstract: We present the development of an automated centrifugal microfluidic platform with integrated sample pre-treatment (filtration and liquid-liquid extraction) and detection (SERS-based sensing). The platform consists of eight calibration and four assay modules, fabricated with polypropylene using injection molding and bonded with ultrasonic welding. The platform was used for detection of a secondary bacterial metabolite (p-coumaric acid) from bacterial supernatant. The obtained extraction efficiency was comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
(15 reference statements)
0
38
0
Order By: Relevance
“…In our previous works, we combined LLE and the here exploited gold-capped silicon nanopillar substrates for extraction and SERS detection of pHCA. 32,33 Besides excluding Tyr and salts, measuring the target analyte in the organic phase (DCM) provided the optimal working conditions for metal-capped nanopillar substrates, since it was demonstrated that wetting the substrate with an organic solvent improves the leaning of silicon nanopillars, 56 leading to a better SERS signal enhancement. With LLE we were able to extract both pHCA and CA from aqueous samples.…”
Section: Lle and Sers For Extraction And Detection Of Phca And Camentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works, we combined LLE and the here exploited gold-capped silicon nanopillar substrates for extraction and SERS detection of pHCA. 32,33 Besides excluding Tyr and salts, measuring the target analyte in the organic phase (DCM) provided the optimal working conditions for metal-capped nanopillar substrates, since it was demonstrated that wetting the substrate with an organic solvent improves the leaning of silicon nanopillars, 56 leading to a better SERS signal enhancement. With LLE we were able to extract both pHCA and CA from aqueous samples.…”
Section: Lle and Sers For Extraction And Detection Of Phca And Camentioning
confidence: 99%
“…30 In spite of the advantages of SERS-based sensing, the presence of interfering compounds and salts represents another issue for quantitative analysis in complex sample matrices, such as bacterial supernatant. 31 To address this issue, we have successfully combined SERS-based sensing with sample pretreatment techniques, such as liquid-liquid extraction (LLE) 32,33 and supported liquid membrane extraction. 34 Sample pretreatment enabled the separation of the target analyte from interfering compounds in the supernatant matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Lab-on-a-chip platforms can be categorized on the basis of their underlying liquid handling principles such as electroosmosis, pressure, peristaltics, ultrasonics, and electrowetting. Centrifugal Along with fluidic functionality, it is critically important that Lab-on-a-Disc cartridges be amenable to mass manufacturing techniques such as injection molding [78]. This work describes the initial development of this mixing structure and the primary manufacturing method, hot embossing, was selected to ensure the designs could easily be translated for manufacture by injection molding.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Alexei et al utilized pneumatic pumping for a multi-cycle LLE process on a centrifugal microfluidic device [19]. Also, Lidia et al performed LLE on a centrifugal microfluidic device with extraction efficiency matching that of conventional batch extraction [20].…”
Section: Introductionmentioning
confidence: 99%